Changes and transformations sports-induced moral transformations in a young adult - Tee Ten, Raphael Francis Gan (College of Engineering, University of the Philippines Diliman, 2013)
What I aim to do in may thesis is to create a novel for young adults. In this novel, the specific topic will be about sports and what it can do to the life of the young adult in the Philippine setting. First, I will attempt to create a novel and not a short story because to create several short stories about sports is too tiring and painful to have to always set up a certain sport. I also notice that doing that may lead to atone that may be too scientific and whatnot. Furthermore, the novel can be divided into parts where there are special chapters for getting into the characters thoughts and attitudes and other chapters solely for the action part of sports. This cannot be done in a short story because studies show that having a very action-packed story may lose the introversion that is so significant for a young adult. Now, what I have done for background research of sports in young adult literature is to get three titles in the genre which deal in specific issues. Inexcusable , one of the titles, deals with the young adult having identify problems as an action he is now infamous for is seeping into his identify as a person. Gym Candy is about the decision to take or not to take steroids and what the repercussions are. Finally, Raiders Night is about the inner workings of the team. These books are my models because they deal with young adults problems. The first on e being the problem of identify where we are struggling with findings out who we really are as person as opposed to our predetermined self that our parents have been instilling in us. The second is peer pressure that can deal with team dynamic and the third is steroids which I will most likely take as a question of morality or, in sports,"how badly do you want it [the gold]? For the Philippine context, I will be relying heavily on my own experiences as a varsity member of the university since there is only one sports Young Adult Novel made by a Filipino but the themes that are discussed in the novel are not as in-depth in the sports world as those presented in the novels above. Also, I will also be pointing to different news articles about sports programs in other countries like the China's controversial Olympic Program and why sports is not succeeding in the Philippines. I will be citing a philosophical paper on morality in my paper as well as I believe this will help in the analysis of the several characters and their decisions. The reason I chose this topic is for the specific reason of finding out whether the myth of "building character" in sports is tru or not. The findings from these novels and studies of the young adults will aid me in my book project in deciding the specific theme and plot for the story.